Continuous application of conservation tillage affects in situ N2O emissions and nitrogen cycling gene abundances following nitrogen fertilization. (June 2021) - Wang, Weiyan; Hou, Yuting; Pan, Wenhui; Vinay, Nangia; Mo, Fei; Liao, Yuncheng; Wen, Xiaoxia
Abstract: Fertilized agricultural soils can be a major source of soil nitrous oxide (N2 O) emissions to the atmosphere. Conservative soil management may have the ability to reduce N2 O emissions through affecting a number of N-cycling-related soil biophysical properties. Using in situ N2 O measurements combined with the techniques of quantitative polymerase chain reaction (qPCR), amplicon sequencing, and metagenomic sequencing, we aimed to understand the effects of long-term (>10 y) conservation tillage (i.e., zero- and chisel-till vs. conventional plow-till) on soil N2 O production and associated microbial guilds following inorganic N fertilizer application in maize. Between 2017 and 2019, continuous in situ measurements of N2 O fluxes indicated that both zero- and chisel-till significantly lowered cumulative emissions within the growing season, compared to plow-till, mainly through shortening the duration and reducing the magnitude of post-fertilization emission events. Conservative soil management, in particular zero-till, consistently increased the Shannon diversity index of bacterial community over the growing season, compared with plow-till. High-frequency qPCR analyses further revealed a clear tillage-induced niche differentiation between nosZI- and nosZII- N2 O reducers, as evidenced by the dominant gene abundance of nosZII compared to nosZI in the conservation tillage soil, which eventually probably contributed to the transformation of N2 O to N2 . Moreover, compared to plow-till, zero-till significantly decreased gene abundances involved in N2 O production including the nirS, nirK, and narG genes, but increased abundances of N2 O reduction genes such as nosZ during peak N2 O emissions. Critically, the abundances of detected species involved in denitrification, such as Deltaproteobacteria_bacterium spp . and Alphaproteobacteria_bacterium spp . were clearly inhibited by zero-till. Overall, the reduced soil N2 O emissions under reduced tillage positively and strongly depended on the nosZI -to- nosZII ratio, while increased emissions due to conventional tillage were positively associated with intensified denitrification. Such improvements in understanding of the responses of N-cycling gene abundances to tillage intensity can certainly help in the development of updated soil management practices and adaptative N application strategies to reduce reactive N emissions in agricultural ecosystems. Highlights: Conservation tillage shortened the duration and lowered the magnitude of post-fertilization N2 O emissions. nosZI, and nosZII genes suggested a tillage-induced niche differentiation among N2 O reducers. Conservation tillage decreased abundance of genes involved in N2 O production. The reduced N2 O emissions were mainly attributed to the low nosZI -to- nosZII ratio. Intensified denitrification resulted in higher emissions of N2 O under conventional tillage soil.